social prejudice against the educator for Early Education - Rosilane do Amaral; Sabrina Züge Romariz; Adirson Olavio Bernardes (Universidade Federal de Santa Catarina, 1999)
The early childhood education institutions, most of them have a prejudice against their male counterparts with children aged 0 to 6 years, this is a function of differentiated instruction for the boy and girl, is the backup data by agencies and socializing agents such as School, Family, teachers with assignment of gender roles and social prescribed in our culture.